Evaluation of Bacteria from Gallus domesticus as a Potential Probiotic in Broiler Chicks: Effects on Growth Performance and Feed Conversion Ratio - Husain, Dirayah Rauf; Dwyana, Zaraswati; Ambeng; Anggraeni, Ayu; Sulfahri (International Journal of Poultry Science, 2017)
Objective: The aim of this study was to isolate, characterize and evaluate the potential of probiotic bacteria from the Indonesian domestic chicken. Methodology: Probiotic bacteria were isolated using the medium Mann Rogosa Sharpe Agar (MRSA). Seven isolates were obtained, five of which had potential as probiotics and were referred to as Probiotic Bacteria (PB): PBA, PBB, PBD, PBE and PBG. A variety of tests were performed to characterize the bacteria, including evaluating their resistance to acidity and bile salts. Results: The results showed that the two isolates of probiotics (PBD and PBG) resistance to acidity (pH 3) and bile salts (5%) could inhibit the growth of the pathogenic bacteria Escherichia coli and Salmonella typhi. Two isolates were selected, PBD and PBG, to give as a probiotic solvent to broiler chickens. A total of 40 broiler chickens were divided into four treatments with 8 repetitions. The treatments were R0 (without probiotic), R2 (probiotic PBD), R3 (probiotic PBG) and R4 (a mixture of probiotics PBD and PBG). The results showed that probiotics containing different bacteria in chicken feed influenced the body weight gain of broilers, but did not significantly affect Feed Conversion Ratio (FCR). The obtained results confirm the effect of probiotic that was isolated from domestic chicken provided increased body weight gain and meat quality. Conclusion: The visual differences found in this study were due to the increased health of the broiler chickens that were given probiotics in comparison to those that were not given probiotics.